A biomechanical comparison of elite swimmers start performance using the traditional track start and the new kick start - Honda, K. E.; Sinclair, P. J.; Mason, B. R.; Pease, D. L. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The international governing body for swimming (FINA) has approved the use of a new starting block (Omega, OSB11) with an inclined kick plate. This has required the development of a kick start technique. The kick plate is angled at 30° to the surface of the block and can move through five different locations on the platform. To date, no study has examined the biomechanical factors associated with a start using the OSB11. Hence, the purpose of this study was to determine the effects of the new start platform on performance, relative to that of the track start. METHODS: The study utilised 14 elite swimmers (nine male aged 20.8 ± 3.0 years, five female aged 21.4 ± 2.8 years) all of which had personal best times which attained a minimum of 850 FINA points. Each completed six dive and glide starts (three kick starts and three track starts) in a randomised sequence. The analysis system calculated the overall force profile of the start. It utilised an instrumented start block including the measurement of the rear foot through a second instrumented incline plate. The system included a series of calibrated high speed digital cameras, one above water to capture the start and three underwater to obtain vision from 0 m to 15 m. A video camera timing system was used to obtain the times to 5 m and 7.5 m. RESULTS: The mean time on block was 0.77 s for the kick start, which was significantly less (p<0.01) than the track start 0.80 s. The kick start was also significantly faster (p<0.05) to 5 m and 7.5 m than the track start (1.62 s & 2.69 s compared to 1.66 s & 2.73 s, respectively). The kick start produced a significantly higher (p<0.01) horizontal take-off velocity (4.48 m/s) compared to the track start (4.41 m/s) and a higher average horizontal force (0.60 N/kg compared to 0.57 N/kg). The average velocity between 5 m and 7.5 m was not significantly different (p>0.05) between the two techniques. DISCUSSION: The results of this study indicate that the kick start on the new OSB11 start platform was significantly faster than the track start. Despite the participant`s own bias towards their preferred technique being the track start, the kick start was significantly faster off the block; with a higher horizontal velocity and an increased on block horizontal force. This advantage was maintained through the time to 5 m and 7.5 m. This preliminary research indicates that coaches and athletes should spend time adapting to the new block and the new starting technique.